Contribuições do cultivo de plantas de cobertura de inverno para qualidade de solos arenosos e relação entre água disponível e densidade em solos de diferentes classes texturais - Santos, Venesa Pinto dos (2023)
Soil quality conditions may differ under specific land use and management due to spatial variability. The use of indicator values for soils different from those present in the database of the indicator raises doubts on its broad application, demanding research to evaluate soil qulaity indicators in different conditions. Soil quality is undoubtedly one of the most important topic to be investigated in Soil Science, in order to identify and quantify the effect of agricultural practices adopted on soil properties. The objective of the first article was to evaluate whether the use of winter cover crops in single and mixed cropping systems improves the quality of two sandy soils in relation to traditional use with winter cereals. Soil quality indicators were studied in two sandy textured soils, comparing cover crop cultivation systems in single species and in mix with white oat cultivation, a traditional commercial winter crop. Physical, chemical and biological properties were evaluated, totaling eleven soil quality indicators related to structure, water retention, water and air conductivity, total carbon and nitrogen content and β-glucosidase enzyme activity. Cover crops compared to the use of traditional winter cereals are more efficient in the short term in improving the quality of sandy texturedsoil. We also provide evidence to suggest that single cropping improve soil texture quality more than a mix of cover crops and winter cereals in the short term. The objective of the second article was to evaluate whether available water (AD) is associated to soil compaction. A database was created with 3940 records obtained from dissertations, theses and other sources of data on Brazilian soils. The strongest associations occurred in the loam (R2 = 029) and very clayey (R2 = 0.27) textural classes, and the delimitation of the database by textural classes was not effective to eliminate the effect of variation in sand and clay fractions on AD. Evidence from this study indicates that soil compaction affects AD to a weak degree, and may increase or decrease AD.